Tendon regeneration and scar formation: The concept of scarless healing. Issue 6 (27th April 2015) - Galatz, Leesa M.; Gerstenfeld, Louis; Heber‐Katz, Ellen; Rodeo, Scott A.
ABSTRACT Tendon healing is characterized by the formation of fibrovascular scar tissue, as tendon has very little intrinsic regenerative capacity. This creates a substantial clinical challenge in the setting of large, chronic tears seen clinically. Interest in regenerative healing seen in amphibians and certain strains of mice has arisen in response to the biological behavior of tendon tissue. Bone is also a model of tissue regeneration as healing bone will achieve the mechanical and histologic characteristics of the original tissue. The ultimate goal of the study of genes and mechanisms that contribute to true tissue regeneration is to ultimately attempt to manipulate the expression of those genes and activate these mechanisms in the setting of tendon injury and repair. Clearly, further research is needed to bring this to the forefront, however, study of scarless healing has potential to have meaningful application to tendon healing. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:823–831, 2015.